Improved measurement of branching fractions for ππ transitions among Υ(nS) states - Bhari, SR; Pedlar, T; Cronin-Hennessy, D; Gao, K; Hietala, J; Kubota, Y; Klein, T; Lang, B; Poling, R; Scott, A; Zweber, P; Dobbs, S; et al. (2009)
Using samples of (5.93±0.10)×106 Υ(3S) decays and (9.11±0.14)×106 Υ(2S) decays collected with the CLEO detector, we report improved measurements of the following branching fractions: B(Υ(3S)→Υ(1S)π+π-)=(4.46±0.01±0.13)%, B(Υ(2S)→Υ(1S)π+π-)=(18.02±0.02±0.61)%, B(Υ(3S)→Υ(1S)π0π0)=(2.24±0.09±0.11)%, B(Υ(2S)→Υ(1S)π0π0)=(8.43±0.16±0.42)%, and B(Υ(3S)→Υ(2S)π0π0)=(1.82±0.09±0.12)%. In each case, the first uncertainty reported is statistical, while the second is systematic. © 2009 The American Physical Society.